2017
DOI: 10.1002/mrm.26892
|View full text |Cite
|
Sign up to set email alerts
|

Tomoelastography of the native kidney: Regional variation and physiological effects on in vivo renal stiffness

Abstract: Tomoelastography provides full field of view maps of renal stiffness with highly detailed resolution and sensitivity to physiological effects related to age and fluid-solid tissue interactions. These basic data could be used to compare pathological conditions in the future. Magn Reson Med 79:2126-2134, 2018. © 2017 International Society for Magnetic Resonance in Medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 47 publications
3
33
1
Order By: Relevance
“…Very few studies have investigated the effect of water intake upon the stiffness of various anatomical regions within the kidney. Marticorena Garcia et al demonstrated an increase in cortex stiffness and decreased medulla stiffness with a water intake of 1 L. The results for cortex are consistent with the current study, in which significant increased stiffness was observed. However, a different observation was found for medulla, whereas we observed an increase in medulla stiffness.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Very few studies have investigated the effect of water intake upon the stiffness of various anatomical regions within the kidney. Marticorena Garcia et al demonstrated an increase in cortex stiffness and decreased medulla stiffness with a water intake of 1 L. The results for cortex are consistent with the current study, in which significant increased stiffness was observed. However, a different observation was found for medulla, whereas we observed an increase in medulla stiffness.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, the stiffness values reported are influenced by the spatial resolution and the ROIs drawn. Also, Marticorena Garcia et al were not clear regarding the time delay before the scan after drinking water. These are a few differences which might have caused the discrepancies in the results reported between the current study and the one conducted by Marticorena Garcia et al…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Values of k ‐MDEV and AHI are based on the assumption of local homogeneity, which is better fulfilled in large and macroscopically homogenous abdominal organs than the mouse brain . Nevertheless, k ‐MDEV has also been demonstrated to be successful in heterogeneous and smaller tissues such as the kidneys, pancreas, and prostate . Heterogeneous inversion methods are being developed and might replace k ‐MDEV in future studies of the mouse brain .…”
Section: Discussionmentioning
confidence: 99%
“…The wave numbers retrieved from multifrequency wave fields can be combined and inverted to compute compound maps of wave speed . This strategy, introduced in the literature as “tomoelastography,” has been demonstrated to be a noise‐robust method for full‐FOV MRE in abdominal and pelvic organs, providing high detail resolution and consistent values with respect to physiological and pathological alterations of mechanical tissue properties in vivo …”
Section: Introductionmentioning
confidence: 99%